Menanamkan Respect Education di Sekolah - Meilani, Renita Puspa; Fitri, Rosa Dwi (Yayasan Darussalam Bengkulu, 2025)
Respect Education is an approach aimed at instilling values of respect, tolerance, and responsibility within educational settings. In schools, this education serves as a vital solution to fostering mutual respect amidst diversity, addressing social conflicts, and reducing bullying behavior. This article aims to identify strategies and implementations of Respect Education in schools, as well as examining its supporting and inhibiting factors. This research employs a qualitative descriptive method by reviewing relevant literature. Findings reveal that the success of Respect Education is influenced by the involvement of multiple stakeholders, the role of teachers as facilitators, and approaches based on local and religious values. The article recommends collaboration between schools, parents, and communities to create a sustainable culture of respect